Evaluation of the effect of the fuel injection phase on the combustion and exhaust characteristics in a diesel engine operating with alcohol-diesel mixtures - VARGÜN, MUSTAFA (My University, 2023)
The purpose of this study is to investigate the effect of the fuel injection phase on the combustion and exhaust characteristics of a diesel engine using alcohol-diesel mixtures. Engine tests were performed by fixing many control parameters to provide homogeneous operating conditions for each cycle. In the result of the study, it was observed that the cylinder gas pressure was improved by advancing the fuel injection timing. Also, the heat release rate rose with an increased alcohol rate in blended fuels. In addition, it was determined that the chemical energy of the fuel is converted into heat energy in a shorter time with the use of alcohol-diesel mixtures. The ignition delay increased by 1.14 o CA with alcohol-diesel blends, while the ignition delay increased by 0.5 o CA with the advancing fuel injection time for all test fuels. Also, a significant decrease occurred in combustion duration with alcohol diesel blends. The knocking tendency increased with the use of blended fuel, and at some point, values obtained with blended fuels were higher than the upper limit. It was monitored that the use of blended fuels caused a significant decrease in CO and NH3 emissions. Moreover, it was detected that changes in the fuel injection timing effectively reduced CO2 and NOx emissions.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Alcohol fuels; diesel engine; fuel injection phase; combustion; exhaust emissions